Pascual Contursi's Lyrics in Tango’s Formal Definition (2022)
Pascual Contursi (1888-1932) is considered the creator of tango-canción and the themes amuros and milonguitas, published in “Mi noche triste” and “Flor de fango” are also considered the foundation of this musical style. However, a stylistic and formal review of his tangos highlights Contursi's crucial contribution to the principles of contrastive symmetry and condensation that consolidated the structure of tango in all of its artistic manifestations. Formally, the strengthening of isometric verses coupled with rhyme on the last syllable, the tension between static description and dynamic narration, the minimalistic setting, the theatrical dialogue of the apostrophe, a counterpoint between the first and second person, as well as the systematic use of lunfardo whose adoption entails, by itself, a contrast against the standard variety of language. Such findings contribute to temper Contursi’s presumed image as a naive and schematic poet.